If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 8) = -10 + 19 Reorder the terms: 3(8 + 5x) = -10 + 19 (8 * 3 + 5x * 3) = -10 + 19 (24 + 15x) = -10 + 19 Combine like terms: -10 + 19 = 9 24 + 15x = 9 Solving 24 + 15x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 15x = 9 + -24 Combine like terms: 24 + -24 = 0 0 + 15x = 9 + -24 15x = 9 + -24 Combine like terms: 9 + -24 = -15 15x = -15 Divide each side by '15'. x = -1 Simplifying x = -1
| 2(0)+y=72 | | 4(5x+4)=-56 | | 35=12y-8y | | 4.2u-5-6.5u= | | -5(n+2)+13=-2n-15 | | 40=4y-16 | | 5x-4+5x-4+2x+3=187 | | 9x-12=-20 | | 8(3v+4)=22-9v | | 3t-3t=-9+9t | | 2(-4z-5)+16=-2(4z-3)+0 | | 17x-4(x-2)=-5 | | 5x-2+10=4x+8+10 | | 3.50=1.90+c | | -24x-31-8x+40x-9=-5x+8+15x | | Inx=-In(x+1) | | 2(3x-1)=x^2+7x-8 | | 26+4y-8=14y-10-3y | | 40*x+(12.5x*1.5)= | | 3.5h=14 | | 2.25(x-42)=x+3.28 | | 2=y/3.2 | | W/4-2=12x^4 | | 11+-12=-25 | | -4(x+3)-3=6(x-6) | | X^2-5x-5=-5 | | -2h+9h=16 | | 23+g=30 | | 10x+3=8x+18 | | 4x-6+5=2+5 | | 5v-17=78 | | 2(-2)+y=72 |